Evaluation of Interprofessional Education (IPE) Among Nursing and Medical Students - Bruce, Shazia; Yar Khan, Muhammad Nadeem; Sani, Sheikh Umer; Shaukat, Ibtesam (Biological and Clinical Sciences Research Journal, 2025)
Interprofessional Education (IPE) is recognized globally as a key strategy in preparing healthcare students for collaborative practice. In Pakistan, however, formal implementation of IPE remains limited despite its potential to improve interdisciplinary teamwork, communication, and patient outcomes. This study evaluates the effectiveness of a structured IPE module among undergraduate nursing and medical students in a Pakistani tertiary care teaching hospital. Objective: To assess changes in students’ perceptions and attitudes toward interprofessional collaboration following participation in a structured IPE intervention. Methods: A quasi-experimental study was conducted from April to September 2024 in a tertiary care hospital. A total of 86 participants (43 nursing and 43 medical students) were enrolled using convenience sampling. A structured four-week IPE module, including case-based learning and team simulations, was implemented. The Interprofessional Education Perception Scale (IEPS) was used before and after the intervention to assess student perceptions across key domains. Data were analyzed using SPSS v25.0, employing paired t-tests and ANOVA to evaluate pre- and post-intervention differences, with p ≤ 0.05 considered significant. Results: There was a statistically significant improvement in overall IPE perception scores post-intervention (mean difference +1.9, p < 0.001). Gains were noted in all subdomains: competency and autonomy (+0.6), perceived need for cooperation (+0.6), and perception of actual cooperation (+0.7). Final-year students exhibited significantly higher post-intervention scores (p = 0.021), while no significant difference was found between nursing and medical students (p = 0.231). Conclusion: Structured IPE significantly enhanced collaborative attitudes and perceptions among nursing and medical students. The findings support the integration of IPE in Pakistani undergraduate health curricula to foster interprofessional teamwork and improve patient-centered care.